Heat Transfer, Volume 1 2006
DOI: 10.1115/imece2006-13552
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics and Heat Transfer in Heat Exchanger Channels With Spherical Holes

Abstract: Results of classification of the existed data on hydrodynamics and heat transfer under forced convection in channels with spherical holes (SHs) are presented. Energy efficiency of the use of SHs under laminar and turbulent flow of a coolant is shown. Effects of regime and design parameters on heat transfer in such channels are studied. The flow-regime chart is developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
4
1
Order By: Relevance
“…Unfortunately, the increase of heat transfer is a companied by an increase in pressure drop [21] resulting in a performance factor increase of 33% in the vicinity of the protrusion. Once again there appears to be contradiction with the work of Leontiev et al [16] who indicate in their (Figure 1) that the performance factor is decreased when a protrusion is introduced in the channel. Similarly to the case of the dimple mentioned above, the reasons for this difference have not been established.…”
Section: Single Protrusioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Unfortunately, the increase of heat transfer is a companied by an increase in pressure drop [21] resulting in a performance factor increase of 33% in the vicinity of the protrusion. Once again there appears to be contradiction with the work of Leontiev et al [16] who indicate in their (Figure 1) that the performance factor is decreased when a protrusion is introduced in the channel. Similarly to the case of the dimple mentioned above, the reasons for this difference have not been established.…”
Section: Single Protrusioncontrasting
confidence: 75%
“…Leontiev and his co-workers [16,17] claimed that heat transfer is significantly increased with dimples in a channel in the same Reynolds number range as that studied by Alshroof et al [13]. They also found that dimples increases the pressure drop.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Structured surface elements -vortex generators of different forms which are applied on heat-exchange surfaces -are promising means for heat transfer intensification in cooling systems of radioelectronic and power equipment and in channels of various power-generating equipment and transportation facilities [11][12][13]. This type of heat transfer intensifiers destroys the laminar boundary layer or the viscous sublayer of the turbulent boundary layer without affecting the main flow and ensures a high thermal and thermohydraulic efficiency [14,15]. The flow past dimples of variable depth under different flow conditions has special features due to the fact that tornado-like vortex structures have two orientations of their axes at the exit from the surface dimple: to the left or to the right, or they are in the stage of change of orientation.…”
Section: Reviewmentioning
confidence: 99%
“…Similarly, Leontiev et al [2006] studied the flow and heat transfer in channels with spherical dimples and proposed 'models' of flow separation in the laminar regime which were functions of the dimple parameters and Re h , the Reynolds number based on the dimple depth. As Re h is increased, the flow appears to separate with the formation of the symmetric vortices about the central axial plane of the dimple.…”
Section: Introductionmentioning
confidence: 99%